Construction of female identies: Narrative about Brazilian women's soccer team in "Globo Esporte" and "Esporte Espectacular" - Nascimento, Isadora (2018)
This research addresses the analysis of the construction of the female identity in the news regarding the Female Brazilian National Soccer Team broadcasted in “Globo Esporte” and “Esporte Espectacular”, from Rede Globo de Televisão, during the 2016 Olympic Games. The identity discussions of Hall (2016), Woodward (2000) and Bhabha (1998); concepts of social representation by Moscovici (2015); the discussion of gender by Scott (1995) and stereotypes of Hall (2016), Bhabha (1998) and Moscovici (2015); as well as discussions regarding the influence of media in contemporary society by Birolli (2011) are highlighted. From the analysis of content by Bardin (2011), contrary to what was expected, there was a creation and diversification of identity models propagated through media, avoiding stereotypical images related to the female identity